Evaluation of heat stress threshold and impacts on milk yield in dairy cattle crossbreds in a hot and humid climate - Michael, Predith; de Cruz, Clement Roy; Mohd Nor, Norhariani; Jamli, Saadiah; Goh, Yong Meng (Springer, 2023)
Heat stress is a major challenge in dairy cattle farming and leads to economic losses. This study aims to determine the impact of heat stress on dairy cattle under a hot and humid climate. Milk yield test records between 2015 to 2019 were collected from 532 first lactating Friesian crossbred cows. Hourly values of temperature (dry bulb), relative humidity, surface wind speed, and solar radiation over 24 h collected from the national weather station in Malaysia were averaged and computed into four temperature indexes (TI). The heat stress threshold was identified using a two-slope broken line regression and the magnitude of milk loss was determined by the degree of decline fitted to a Legendre polynomial regression. Environmental parameters and TI values were observed to be influenced by the dry and monsoon season. Thresholds reported ranged between 73 (TI4) to 79 (TI3) according to the respective TI measured. The index values were higher than the reported studies in temperate, semi-arid and mediterranean climates. The largest milk decline was determined as 0.181 kg in mild, 0.267 kg in moderate, and 0.523 kg in extreme heat stress conditions, respectively, when using the conventional TI1. Thresholds determined in the current study can be used for annual forecasting and targeted heat stress mitigation efforts.